Informe de línea de base : indicadores de impacto - John, Beer; Gutiérrez Montes, Isabel A.; Mercado, Leida; Aguilar, Amílcar; Padilla Castillo, Danilo; Somarriba, Eduardo; Cerda Bustillos, Rolando (CATIE, Turrialba (Costa Rica), 2016)
45 páginas, 7 ilustraciones, 21 tablas